Toward a Systematic Approach to Developing Professional Roles: What Writing Tutors Need to Know and Know How to Do - Dagmar Knorr; Micha Gerrit Philipp Edlich (Hermes)
The ability to write well in academic context is usually the result of a long and uneven learning process that requires commitment, persistence, and, ideally, formal training. Professionals tasked with supporting academic writers, for example writing center staff or peer writing tutors, not only are expected to write well but also need to learn how to facilitate the individual development of their clients. To prepare peer tutors for this role, many writing centers have developed training programs. Contributing to the literature on this specific dimension of writing center work, this article introduces a design of a training program that considers the different knowledges that writing tutors need to have so that they can support their clients. Based on the Systemization Writing Consultations, this program identifies key educational objectives for new tutors and prepares participants for further systematic individual development over the course of the training and beyond. Emphasizing the importance of reflection in this respect, this article discusses several approaches and strategies that allow participants to reflect on their writing and their future role as peer writing tutors. The training discussed here is not only of interest to writing center directors and staff but also to professionals in similar contexts tasked with designing and running programs and interventions geared toward the long-term development of professional skills and roles.